1987
DOI: 10.1002/bbpc.19870911205
|View full text |Cite
|
Sign up to set email alerts
|

The static structure factor of cesium over the whole liquid range up to the critical point

Abstract: The paper presents the first neutron scattering investigation of the static structure factor S(Q) of expanded liquid cesium from the melting point up to its critical point at conditions near the liquid‐vapour coexistence curve (critical data of cesium: Tc = 1924 K, pc = 92.5 bar, dc = 0. 379 g/cm3). The characteristic changes of the microscopic structure — such as the distance and number of nearest neighbours — are derived as a function of density. The reported results give useful information about the density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(63 citation statements)
references
References 25 publications
7
55
1
Order By: Relevance
“…It is quite evident that our observation is different from those of the previous observations [10,11] in which microscopic structural variation is essentially similar to that of rare-gas liquids. The shortening of r 1 is seemingly consistent with the appearance of diatomic molecules as suggested by the inelastic neutron scattering measurements [20].…”
Section: Article In Presscontrasting
confidence: 99%
See 2 more Smart Citations
“…It is quite evident that our observation is different from those of the previous observations [10,11] in which microscopic structural variation is essentially similar to that of rare-gas liquids. The shortening of r 1 is seemingly consistent with the appearance of diatomic molecules as suggested by the inelastic neutron scattering measurements [20].…”
Section: Article In Presscontrasting
confidence: 99%
“…They reported that the local structure of expanded fluid Rb changes in the way that is similar to that of simple liquids; the coordination number decreases linearly while the nearest-neighbor distance is almost unchanged or slightly increased. Winter et al [11] carried out neutron diffraction measurements for fluid Cs and reported the local structural variation essentially similar to that of fluid Rb.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For many decades there have been almost no structural studies of supercritical metallic fluids except for fluid Rb and Cs. The static structure factor S(Q) as well as S(Q, E) of fluid Rb and Cs, whose critical pressures are low compared to that of, namely, fluid Hg, were investigated in the pioneering works of Hensel and co-workers using neutrons [7]. About two decades ago Tamura and Hosokawa developed a high-pressure vessel with Be windows and a specially designed sapphire cell for X-ray diffraction measurements of supercritical fluid Hg [8].…”
Section: Introductionmentioning
confidence: 99%
“…Before summarizing, we want to mention the initial motivation for the studies of quasi-one-dimensional systems by Schmidt and Springborg [4] and for our own alkali metal investigation [1]. In [4] it was noted that the channels in zeolite constrained Pb/Bi to almost linear chains (these one-dimensional structures are very soft and their geometry can be easily influenced by weak external perturbations such as those of the zeolite walls or surfaces), while in [1] the motivation was provided by neutron scattering studies of fluid metal Cs along the liquid±vapour coexistence curve towards the critical point by Hensel and coworkers [10,11]. Their finding was that the major reason for the lowering of density towards the critical point was the lowering of coordination number c, the bond length r 0 increasing by only tenths of an # e. At a given bond length, and (1) as a function of the near-neighbour bond length (see inset for structure labeling).…”
Section: Discussionmentioning
confidence: 98%